Moderating role of trade openness between export upgrading and economic growth - Shamrez Ali; Qaiser Munir (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
The present research analyzes the nexus between export upgrading and economic growth. In addition, it studies the moderating role of economies' level of openness to international trade between export upgrading and economic growth for a group of 131 countries covering the period of 2006-2019. The Generalized Method of Moment (GMM) is used for empirical analysis in STATA. Findings of this study express that export upgrading has a positive impact on economic growth. However, empirical results based on the developed and developing countries, show that although export upgrading has a positive impact on economic growth in developing economies, its effect is insignificant for developed economies. Unlikely, trade openness enhances the impact of export upgrading on economic growth in developed economies, however; it reduces this impact in developing economies.
Keywords: 330; export sophistication; export upgrading; trade openness; economic growth